Remarks on codex crimes of capital fraud art. 311 CC in the background of neighbouring countries - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The subject of the article is the presentation of the genesis of criminalisation of capital fraud in the Polish Criminal Code. Further edits of the projects of this crime in the drafts of the current Criminal Code are also analysed, as well as the scope of criminalisation and the problem of repression of capital fraud in Polish criminal law. In addition, solutions proposed to criminalise capital fraud in neighbouring countries are presented. These analyses provide the basis for reporting significant legislative changes.
Keywords: oszustwo kapitałowe; oszustwo gospodarcze; przestępczość gospodarcza; prawo karne gospodarcze; porównawcze prawo karne gospodarcze